Regulatory T Cells in Chronic Heart Failure - Lu, Yuzhi; Xia, Ni; Cheng, Xiang (Frontiers in Immunology, 2021)
Heart failure is a global problem with high hospitalization and mortality rates. Inflammation and immune dysfunction are involved in this disease. Owing to their unique function, regulatory T cells (Tregs) have reacquired attention recently. They participate in immunoregulation and tissue repair in the pathophysiology of heart failure. Tregs are beneficial in heart by suppressing excessive inflammatory responses and promoting stable scar formation in the early stage of heart injury. However, in chronic heart failure, the phenotypes and functions of Tregs changed. They transformed into an antiangiogenic and profibrotic cell type. In this review, we summarized the functions of Tregs in the development of chronic heart failure first. Then, we focused on the interactions between Tregs and their target cells. The target cells of Tregs include immune cells (such as monocytes/macrophages, dendritic cells, T cells, and B cells) and parenchymal cells (such as cardiomyocytes, fibroblasts, and endothelial cells). Next-generation sequencing and gene editing technology make immunotherapy of heart failure possible. So, prospective therapeutic approaches based on Tregs in chronic heart failure had also been evaluated.